Tinospora crispa Phytosome Enhances Oral Bioavailability and Glycemic Control in Streptozotocin-Induced Diabetic Rats - Dedi Sucipto; Taufiq Indera Jayadi; Bryan Helsey (HM Publisher, 2026)
Diabetes mellitus remains a major global health challenge with rising prevalence in Southeast Asia, where traditional herbal remedies continue to play a significant role in disease management. Tinospora crispa (L.) Hook. f. & Thomson (Menispermaceae), locally known as brotowali in Indonesian jamu medicine, exhibits anti-diabetic properties attributed to its alkaloid and diterpenoid constituents; however, the oral bioavailability of its key bioactive compound berberine remains limited at approximately 5%. This study evaluated the pharmacokinetic enhancement and anti-diabetic efficacy of a novel Tinospora crispa phytosome in streptozotocin (STZ)-induced diabetic rats. Thirty male Wistar rats were allocated to five groups (n = 6): normal control, diabetic control, diabetic plus metformin (200 mg/kg), diabetic plus T. crispa free extract (400 mg/kg), and diabetic plus T. crispa phytosome (400 mg/kg), given orally for 28 days. The phytosome achieved a 3.14-fold enhancement in relative oral bioavailability (AUC0–24: 1524.7 ± 185.4 versus 486.3 ± 62.8 ng·h/mL, p < 0.001) and a higher peak plasma berberine concentration (Cmax: 387.2 ± 42.3 versus 124.5 ± 18.7 ng/mL, p < 0.001). After 28 days, the phytosome group showed significant reductions in fasting blood glucose (148.6 ± 19.2 versus 328.4 ± 42.5 mg/dL, p < 0.001) and HbA1c (6.1 ± 0.6 versus 9.2 ± 1.1%, p < 0.001), with an improved lipid profile comparable to metformin and large effect sizes (Cohen's d: 3.51–6.22). These findings indicate that phytosome technology effectively enhances the bioavailability and anti-diabetic efficacy of T. crispa, supporting its development as a standardized herbal complementary therapy for diabetes mellitus.